Prevalence of youth gambling and potential influence of substance use and other risk factors throughout 33 European countries: first results from the 2015 ESPAD study. (5th July 2018) - Molinaro, Sabrina; Benedetti, Elisa; Scalese, Marco; Bastiani, Luca; Fortunato, Loredana; Cerrai, Sonia; Canale, Natale; Chomynova, Pavla; Elekes, Zsuzsanna; Feijão, Fernanda; Fotiou, Anastasios; Kokkevi, Anna; et al.
Abstract: Background and aims: Although generally prohibited by national regulations, underage gambling has become popular in Europe, with relevant cross‐country prevalence variability. This study aimed to estimate the prevalence of underage gambling in Europe stratified by type of game and on‐/off‐line mode and to examine the association with individual and family characteristics and substance use. Design: Our study used data from the 2015 European School Survey Project on Alcohol and Other Drugs (ESPAD) cross‐sectional study, a survey using self‐administered anonymous questionnaires. Setting: Thirty‐three European countries. Participants: Sixteen‐year‐old‐year‐old students ( n  = 93 875; F  = 50.8%). Measurements: The primary outcome measure was prevalence of past‐year gambling activity. Key predictors comprised individual behaviours, substance use and parenting (regulation, monitoring and caring). Findings: A total of 22.6% of 16‐year‐old students in Europe gambled in the past year: 16.2% on‐line, 18.5% off‐line. High prevalence variability was observed throughout countries both for mode and types of game. With the exception of cannabis, substance use shows a higher association with gambling, particularly binge drinking [odds ratio (OR) = 1.46, 95% confidence interval (CI) = 1.39–1.53), life‐time use of inhalants (OR = 1.57, 95% CI = 1.47–1.68) and other substances (OR = 1.78, 95% CI = 1.65–1.92)]. Among life habits, the following showed a positive association: truancy at school (OR = 1.26, 95% CI = 1.18–1.35), going out at night (OR = 1.32, 95% CI = 1.26–1.38), participating in sports (OR = 1.30, 95% CI = 1.24–1.37). A negative association was found with reading books for leisure (OR = 0.82%, 95% CI = 0.79–0.86), parents' monitoring of Saturday night activities (OR = 0.81, 95% CI = 0.77–0.86) and restrictions on money provided by parents as a gift (OR = 0.89, 95% CI = 0.84–0.94). Conclusions: Underage gambling in Europe appears to be associated positively with alcohol, tobacco and other substance use (but not cannabis), as well as with other individual behaviours such as truancy, going out at night and active participation in sports, and is associated negatively with reading for pleasure, parental monitoring of evening activities and parental restriction of money.